Environmental Impact of Ground Source Heat Pump Systems: A Comparative Investigation From South to North Europe - Aresti, Lazaros; Florides, Georgios A.; Skaliontas, Andreas; Christodoulides, Paul (Frontiers in Built Environment, 2022)
Ground Heat Exchangers (GHEs), which are buried in the ground either horizontally or vertically (in a borehole), when coupled with a heat pump, form a Ground Source Heat Pump (GSHP) system, a type of Renewable Energy System that exploits geothermal energy for space heating and cooling. GSHP systems are proposed as an alternative to conventional Air Source Heat Pumps (ASHPs) as they exhibit a higher efficiency. In this study, this difference in efficiency is tested in order to determine how the systems perform in terms of environmental impact. Three types of GSHP systems (with different GHE configuration), each compared to ASHPs, undergo a Life Cycle Analysis using the ReCiPe method from both mid-point and end-point perspectives. The heating and cooling loads required for a single residential building of area 220m2, with nearly Zero Energy Building technical characteristics, is used as a Functional Unit , for seven cases (locations/countries) from South to North Europe. Additionally, a Simple Payback Period method is employed to investigate the CO2 payback time for the GSHPs. It is concluded that the use of GSHP systems in residential buildings, even with nZEB characteristics of low heating/cooling demand, can be a more environmentally friendly solution than that of an ASHP system, depending on the factors affecting the system, namely the ground thermal characteristics, the heating/cooling demand, the heating/cooling peak loads and electricity mix.